Madelung Deformity - Esthetic and Functional Outcomes from the Surgical Treatment with Distal Radial Dome Osteotomy and Vickers Ligament Section - Marcos Carvalho; Pedro Sá Cardoso; Cristina Alves; Inês Balacó; Tah Pu Ling; Gabriel Matos (Revista Brasileira de Ortopedia, 2022)
Abstract Objective The present study aimed to evaluate esthetic and functional outcomes from the surgical treatment of Madelung deformity in children. MethodThis is a retrospective study of pediatric patients with Madelung deformity who were surgically treated with dome osteotomy of the distal radius and Vickers ligament section from 2015 to 2018. Patients with a minimum postoperative follow-up period of 12 months were included. Demographic data, surgical technique, clinical and radiographic outcomes were analyzed. Pre and postoperative radiographic evaluation consisted of ulnar tilt, lunate subsidence lunate fossa angle, and palmar carpal displacement measurements. The postoperative clinical evaluation consisted of ranges of motion of the wrist, visual analog scale (VAS) and Disabilities of the Arm, Shoulder and Hand (DASH) score. Results Four patients were included, two with idiopathic Madelung deformity and two with bone dysplasia. All patients were females and presented bilateral disease. Six wrists were operated on. The median age at surgery was 15.5 years old, and the median postoperative follow-up time was of 37.5 months. The postoperative radiographic analysis revealed an average correction of 8.8 ± 7.5° for ulnar tilt, 3.0 ± 3.9 mm for lunate subsidence 8.2 ± 6.6° for lunate fossa angle, and 4.7 ± 2.6 mm for palmar carpal displacement. Average postoperative ranges of motion of the wrist joint were 75.8 ± 3.4° for flexion, 62.5 ± 14.1° for extension, 25.7 ± 2.9° for radial deviation, 40.0 ± 2.9° for ulnar deviation, 88.3 ± 2.4° for pronation, and 82.5 ± 2.5° for supination. The median VAS was 1 for residual pain, 0 for functional deficit, 0 for esthetic impairment, and 10 for recommending the surgical procedure. The median DASH score was 0. Conclusion Madelung deformity treatment using dome osteotomy of the distal radius and Vickers ligament section results in excellent esthetic and functional outcomes.